(untitled) (Global Journal of Science Frontier Research, 2014)
Plantain of Guinea". The Atlantic Adventure of Banana. It is studied the historical process of the first move of Musaceae to the West Indies, along with sugarcane, in the context of a transatlantic network. Historical texts are critically analysed; evidence about cultivations and species in Europe, Africa and the archipelagos in Macaronesia is shown; longterm historical mistakes are discussed and some hypotheses about the Atlantic transport of biotypes or hybrids during the sixteenth century are suggested.